Chemical Characteristics of Acid Sulphate Soil at Various Depths of Sulfuric Layers and Their Impact on The Development of Oil Palm Plant Roots - Noviandi Ginting, Eko; Sigit Sutarta, Edy (Jurnal Penelitian Kelapa Sawit, 2024)
One limitation of using acid sulfate soil for oil palm cultivation is the presence of a sulfuric layer that has the potential to oxidize. The sulfuric layer’s oxidation can make the soil acidic and release harmful metals that might inhibit plant roots from growing. This study aims to investigate the chemical properties of soil in oil palm plantation blocks with varying sulfuric depths and their impact on the vertical growth of oil palm roots. The objects of this research study are three plant blocks, namely Block 27, Block 41, and Block 42, each with a sulfuric layer depth of 40-60 cm, 60-90cm, and > 90 cm, respectively. The research findings indicate that the acidity level, exchangeable Al, and Fe content in the soil of Block 27 are relatively higher compared to the other blocks. The amount of exchangeable Al and Fe in the soil is correlated with the pH of the soil, where lower pH values correspond to higher exchangeable Al and Fe content in the soil. The block with the highest total oil palm root development was Block 41, measuring 188.26 g/dm3, while the block with the lowest was Block 27, measuring 75.99 g/dm3. According to the study’s findings, the shallower sulfidic layer, the more hampered the development of oil palm roots. Oil palm root development is optimal when the sulfuric layer depth exceeds 90 cm.